Uji Kinerja Alat Pengering Tipe Batch Dryer untuk Pengeringan Kakao (Theobroma cacao L.) dengan Sistem Penghembus Udara Panas - Akbar, Suseno Ali; Asmara, Sandi; Kadir, M. Zen; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2024)
Cocoa is a superior export commodity for Indonesia. Lampung is one of the largest cocoa producing regions in Indonesia. In processing cocoa beans, drying is the most important factor for quality. The causes of the low quality of cocoa beans include unfermented cocoa beans before drying and the conventional drying process. Drying of cocoa can be done using a bacth type dryer with a hot air blower system with a large enough capacity that has been built on offer. This study aims to examine the performance of batch type cocoa dryers with hot air blowing systems. The method used in this study is an experimental and descriptive method that uses cocoa with different initial moisture content, namely 36.62%, 42.20%, and 32.61%. The results showed that the batch type dryer produced plenum temperature of 590 C, 580 C, 620 C and the temperature of the material that was 500 C, 500 C, and 510 C. The higher the temperature used, the faster the drying time and the lower the initial temperature of cocoa the faster the drying process. Rubber wood fuel used in each test is 101 kg, 123 kg, 95 kg. Drying time for all three tests is 10 hours, 11 hours, and 10 hours. The efficiency of drying using batch type dryer is 26.01%, 26.75%, 25.52%. The weight of 1 kg of rubber wood on average can dry 5 kg of wet cocoa Keywords: Bath Type Dryer, Cocoa, Moisture Content, Temperature.